The Management of Education Operational Grant and Its Effects on School Development - Lubis, Reniwati; Irfana, Tungga Buana; Purwatiningsih, Sri; Nisak, Sayida Khoiratun; Sari, Vivi Puspita (Academy of Education Journal, 2024)
This study aims to describe how BOS funds can improve educational quality in Indonesia, with a particular focus on developing facilities and infrastructure in schools to enhance student learning. To achieve these objectives, a literature review research method was employed, namely the study of the concepts and theories used based on the available literature. The results of the literature review demonstrate that the optimal implementation of the eight education standards through BOS funding is conducive to realizing the advancement and enhancement of educational quality in academic institutions. The improvement of educational quality in schools must include the development of the eight standards, and the operationalization of these standards is contingent upon financial resources. This study also examined how schools utilize government assistance funds, including their allocation for the fulfillment of these needs. Thus, BOS funds have a pivotal, strategic, and contributory role in the seamless and efficacious implementation and enhancement of educational quality.